Characterization of Some metal Complexes of Thiazolidine-4-Carboxylic Acid - Sinha, B.k.; Prasad, S.N.; Prasad, Ramdeo; Srivastava, Miru; Kumar Yadav, Suresh (Asian Journal of Chemistry, 2010)
A series of metal complexes of thiazolidine-4-carboxylic acid(prepared by Ratner and Clarke procedure) were synthesised inneutral or in alkaline medium at pH 8.0. The stoichiometries of themetal compounds were established on the basis of elemental analysisand metal content determination. Magnetic measurements haveshown that iron forms ferromagnetic compound, Cobalt(lI) highspin octahedral complex, nickel a tetrahedral surrounded with octahedralspecies and copper a dimer on account of sulphur exchangemechanism. The IR spectra on interpretation have shown that metalsare bonded at N of NH group and oxygen of COO group of theligand.